2014
DOI: 10.1097/dbp.0000000000000036
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Provider Perspectives on Procedural Care for Children with Autism Spectrum Disorders

Abstract: Children with autism spectrum disorders require individualized interventions to maximize the quality of procedural care. However, many hospitals and providers are not sufficiently equipped to accommodate these children's needs. This study suggests that targeted improvements in preparation and communication between providers and families as well as modifications in patient flow and clinical environments have the potential to improve the quality and successful completion of procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
77
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 20 publications
5
77
0
Order By: Relevance
“…Recent empirical research has supported this link between sensory processing and dental care difficulties in children with ASD (Stein et al, 2011; Stein et al, 2013; Stein et al, 2014). Likewise, sensory challenges have been reported to occur in other healthcare environments, such as the hospital (Davignon et al, 2014; Muskat et al, 2014), primary care (Pfeiffer & Stein, 2016), and the emergency room (Giarelli et al, 2014). If dental professionals are aware of and understand the potential impact of sensory sensitivities on children with ASD, there are many adaptations that can be made to help the child and their family feel more comfortable with care.…”
Section: Discussionmentioning
confidence: 99%
“…Recent empirical research has supported this link between sensory processing and dental care difficulties in children with ASD (Stein et al, 2011; Stein et al, 2013; Stein et al, 2014). Likewise, sensory challenges have been reported to occur in other healthcare environments, such as the hospital (Davignon et al, 2014; Muskat et al, 2014), primary care (Pfeiffer & Stein, 2016), and the emergency room (Giarelli et al, 2014). If dental professionals are aware of and understand the potential impact of sensory sensitivities on children with ASD, there are many adaptations that can be made to help the child and their family feel more comfortable with care.…”
Section: Discussionmentioning
confidence: 99%
“…Put simply, when unaware to the child's disability, the nurses did not have the chance to specifically prepare for the child. Previous research has revealed that the absence of any structure in place for preparation, the knowledge and the attitude of the nurse can only help a child with ASD to a limited extent (17,24,29,30). This study's findings occasionally revealed special and experienced staff working with these children in certain departments.…”
Section: Discussionmentioning
confidence: 79%
“…This would help to prevent noncompliant behavior from the child (17,33,34). Davignon et al (2014) found that alterations in the organization and administration of healthcare services is essential for the successful care of children with ASD (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autism spectrum disorders occur in 1 of 68 children, and children with autism spectrum disorders have a higher likelihood of needing medical services than do normally developing children . Many medical services such as radiologic imaging, neurophysiologic studies, phlebotomy, and other procedures require procedural sedation . Children with autism spectrum disorders pose challenges for sedationists and anesthesiologists because of a variety of behavioral, sensory, and communication issues .…”
Section: Introductionmentioning
confidence: 99%